Corporate Waqf University: a sustainability model / Ridzwan Bakar ... [et al.] - Bakar, Ridzwan; Sakinah, Wardah; M Zaini, Rapiah; Sarmin, Farzana (Universiti Teknologi MARA Selangor, 2019)
Globalization and economic pressure faced by governments including Malaysia, have led universities to be independent and source out their own fund for development, operation and research activity. In Malaysian case, the government has launched National Higher Education Strategic Plan Beyond 2020 to prepare for new challenges. As a result, the plan offers new autonomy for public universities. While government gives special attention to public university, literature provides limited discussion on the funding and sustainability of private universities. As such, this paper aims at exploring waqf as one of the financing instruments for private university’s sustainability. The paper proposes conceptual model to transform conventional method of financing university into corporate waqf university (CoWU), based on Yayasan Universiti Multimedia (YUM) experience. The study expands previous research and highlights the potential of transforming existing conventional endowment to Islamic endowment (waqf). The study adopts qualititative approach where desk research, interview, discussion, benchmarking as well as primary data collection were employed. It opens up possibilities and proposes practical model where corporate sector and university can work together to establish and fund corporate waqf university. The study also examines issues in implementing corporate waqf university, discusses opportunities and challenges in managing waqf for higher learning institutions. Finally, the paper suggests some pertinent points for policy maker and practitioner consideration.